Odpowiedzi

2009-09-25T17:29:59+02:00
Rozwiąż równanie:
a)2x(x-1)=2(x-1)(x+3)
2x²-2x=2(x²+3x-x-3)
2x²-2x=2x²+6x-3x-9
-2x=3x-9
-5x=-9
x=9/5
x=1,8
ROZWIĄŻ UKŁADY RÓWNAŃ:
a)
{ 3x-1=y-2
4x-3=-2(y-2)

{ 3x-1=y-2
4x-3=-2y+4

{ 3x-y=-2+1
4x+2y=4+3

{ 3x-y=-1 /2
4x+2y=7

{ 6x-2y=-2 /2
4x+2y=7

10x=5
x=0,5
y=2,5

1 5 1
2009-09-25T17:30:38+02:00
A)2x²-2x=2x²-2x+6x-6
x=1

b)3x-1=y-2 / *2
4x-3=-2y+4

6x-2=2y-4
4x-3=-2y+4

10x-5=0

x=0,5

y=2,5
1 5 1
  • Użytkownik Zadane
2009-09-25T18:24:20+02:00
A)2x(x-1)=2(x-1)(x+3)
2(x*x-x)=2(x-1)(x+3)
x*x-x=x*x+3x-x-3
x*x-x*x-x=2x-3
-x-2x=-3
-3x=-3
-x=-1
x=1

a)
{ 3x-1=y-2
4x-3=-2(y-2)

{ 3x-y=-2+1 ||*2
4x+2y=4+3

+ { 6x-2y=-2
4x+2y=7

10x= 5
x=0,5

4*0,5+2y=7
2y= 5
y=2,5
1 5 1